Pengaruh Komunikasi dan Keterampilan terhadap Efektivitas Kerja Bidan di Puskesmas Sukaluyu Kabupaten Cianjur - Aprilliasari, Diah; Andriani, Rian; Asril, Juli (Jurnal EMT KITA, 2026)
Work effectiveness is one of the goals of every job execution. Factors influencing work effectiveness include worker characteristics, among which are communication and skills. Midwife communication and skills do not operate independently but rather support each other. A midwife with high technical skills but lacking in communication may struggle to convey information or build good relationships with patients, which ultimately can reduce the effectiveness of her services. Conversely, a midwife who is communicative but technically less competent will also not provide optimal service. Both are crucial and complementary aspects in providing quality midwifery services. The purpose of this study is to determine the influence of communication and skills on effectiveness of midwife’s work at Sukaluyu Community Health Center, Cianjur Regency. The population of this study was 33 people. The sampling technique used was total sampling. This research is a cross-sectional study. The statistical instruments used were regression analysis, employing validity, reliability, and normality tests. Based on the research results, it shows that there is an influence of communication and midwife skills on work effectiveness at Sukaluyu Community Health Center, Cianjur Regency, amounting to 40,8%, while the remaining 59.2% is influenced by other factors not examined in this study.